Modelling and simulation of wireless information and power exchange protocol with power splitting for energy sustainability in device-to-device communications - Mansoor, Ibrahim Adeeb (2019)
Wireless Information and Power Exchange (WIPE) protocols are very important on the Internet of thing (IoT) wireless sensor communication. With this scheme, the nodes can control and manage their power. Also, with the scheme, one will know which nodes consume more powers and which nodes consume fewer powers. To understand the WIPE protocol and operating system, this research was explored the system operation of WIPE protocol and studied the power splitting among all the nodes. In this study, MATLAB coding was used and the user is allowed to enter the network size and the number of nodes in the program. With these two parameters, the MATLAB plots the location of nodes randomly within the size defined by the user and plots the power splitting as well as displays the power and energy consumed by each node. It is suggested, when the nodes are not sending any message, they can go into sleep mode to save energy. The nodes only wake up when they want to send or communicate with other nodes. In this study, the RF energy harvesting technology was used to power-ups all the wireless sensor nodes wirelessly. At the end of the research, graphs displaying the number of nodes and the size of the network that affect the power splitting, power consumption and energy used were analyzed.